Supporting Factors in Forming Islamic Village-Owned Enterprise (I-BUMDes) in Nagan Raya District - Wahyuddin; Arroyan Ramly; Muslim A Djalil; Mirna Indriani (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
It is important and urgent to conduct a scientific study on the establishment of Islamic Village-Owned Enterprises (I-BUMDes) through the local potential to realize independent villages, by analyzing local potential variables, financial capital, human resources, and community participation in the establishment of I-BUMDes in Nagan Raya District. The population of this study was all villages that have Bumdes in Nagan Raya district. The sampling technique used was purposive sampling. The study sample was 10 I-BUMDes that have run in Nagan Raya district. Primary data was obtained by interviews and questionnaires to I-BUMDes administrators and communities in the local area. Secondary data was obtained from the Central Bureau of Statistics (BPS), Regency Community Empowerment Agency (BPM), and the internet. Regression analysis was performed to determine whether an independent variable has an effect on the dependent variable by using the regression model estimation by entering a dummy variable, the joint hypothesis test model. Significance test was carried out using the normality test method through the Jarque-Bera (JB) statistical test through histogram screening, with a significance level of 5% indicating that the statistical value was 163,393 while the square chi value α = 5% and (df = n-2 = 130-2 = 128, α = 5%). Therefore, the Ho assumption is accepted which means the norm is distributed data. The regression results using qualitative variables can be seen, showing different results and in accordance with the hypothesis that was built. The regression results by entering the dummy variable show a positive and significant effect at α = 5%, towards the formation of I-BUMDes in Nagan Raya District. Only human power variables do not affect the formation of I-BUMDes with an error term value of α = 5%.